2022
DOI: 10.1371/journal.pone.0273351
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study of anterior and posterior pelvic rings using pedicle screw fixation for Tile C1 pelvic fractures: Finite element analysis

Abstract: Objective The purpose of this study was to analyse the biomechanical characteristics of pedicle screws with different placement methods and diameters in the treatment of Tile C1 pelvic fractures by finite element simulation technology and to compare them with the plate fixation model to verify the effectiveness of pedicle screw fixation. Methods A three-dimensional digital model of a normal pelvis was obtained using computed tomography images. A finite element model of a normal pelvis containing major ligame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The peak stress of the implant was lower than the yield stress in both models, suggesting that the 2 fixation methods for the treatment of unstable pelvic ring injuries could be safe. The results were in concordance with those of Song et al [ 13 ] who conducted a biomechanical study on the treatment of Tile C1 pelvic fractures and found that the maximum stresses of the ilium and implant in the pedicle screw model were less than those in the plate model. In another biomechanical study, Salášek et al [ 25 ] demonstrated that the pedicle screw construction experienced lower stress than 2 sacroiliac screws.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The peak stress of the implant was lower than the yield stress in both models, suggesting that the 2 fixation methods for the treatment of unstable pelvic ring injuries could be safe. The results were in concordance with those of Song et al [ 13 ] who conducted a biomechanical study on the treatment of Tile C1 pelvic fractures and found that the maximum stresses of the ilium and implant in the pedicle screw model were less than those in the plate model. In another biomechanical study, Salášek et al [ 25 ] demonstrated that the pedicle screw construction experienced lower stress than 2 sacroiliac screws.…”
Section: Discussionsupporting
confidence: 91%
“…[ 6 , 11 ] To address these limitations, the pedicle screw construction has been introduced as an alternative to treat posterior pelvic ring injuries. [ 13 ] Bi et al [ 5 ] clinically compared the pedicle screw construction with the LCP in a retrospective study and observed that the size of incision, operation duration and bleeding volume were statistically smaller in the pedicle screw group than in the LCP group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations